Micro-credentials for employers : guidelines in reskilling workforce impacted by the changes caused by disruptive technologies - Steyn, Adriana Aletta (Riana) (University of Pretoria, 2024)
Dissertation (MIT (Information Systems))--University of Pretoria, 2024.